Development of Learning Modul on the Work Based Learning Learning Model the Teaching Factory Concept (WBL-TEFA) in Automotive Vocational Learning - maksum, Hasan; Sugiarto, Toto; Hidayat, Nuzul; Siman, Siman; Hasan, Hanapi (PAKAR Pendidikan, 2024)
This research is based on the results of a preliminary study which found the problem that learning was not optimal. The aim of the research is to develop the WBL-TEFA Learning Model Learning Module as an effort to improve valid, practical, and effective automotive vocational student academic achievement skills and task skills. The research method is Research and Development using the Borg & Gall development procedure. After implementing the WBL-TEFA Learning Module, students can build knowledge inductively and deductively, as well as learning experiences in one-way interaction, personal interaction and multi-way learning interaction. The results of this research generally produce a learning module design consisting of covers, prefaces, table of contents, module position maps in learning, glossary, pre-learning, learning, evaluation, and closing. Learning Module The WBL-TEFA Learning Model is statistically valid and practical. Whereas the average Aiken's V value obtained is 0.941, so that the contents of the Learning Module can be declared in the valid category. The WBL-TEFA Learning Module was stated to be very practical, this was shown from the results of the practicality assessment of the average lecturer response of 91.29% and student response of 89.60% in the "Very practical" category.